Kualitas Laporan Keberlanjutan: Eksistensi dari Media dan Industri - Tizmi, Salsabila; Luthan, Elvira; Rahman, Annisaa (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p12, 2022)
The purpose of this study is to determine the effect of media and industry to the quality of sustainability report disclosure. Media is identified by online and social media. The amount of unfavorable news stories in Kompas and Detik is used to quantify online media. The amount of likes, comments, and tweets on Facebook, Twitter, and Instagram is used to quantify social media. The term industry refers to the sort of industry. GRI G4 Index is used to assess the sustainability report's disclosure. This study employs 37 firms as a sample that have gone public and are listed on the BEI in 2017-2020. Purposive sampling is used to determine the sample size.   The data analysis technique in this study uses multiple linear regression. The study's findings indicate that online media, social media, and industry type all have a major impact on the quality of sustainability report disclosure. Keywords: Sustainability Report Disclosure; Online Media; Social Media; Type Of Industry .